Assessing the Computational Thinking of Pre-Service Teachers: A Gender and Robotics Programming Experience Analysis - Lourdes Villalustre; Marisol Cueli (Education Sciences, 2023)
Computational thinking has provided a new logical approach to teaching programming. However, certain variables, such as gender and previous experience in robotic programming, may influence its development. The present study was aimed to (1) characterise 164 infant and primary education pre-service teachers in terms of their level of computational thinking, (2) analyse whether there are statistically significant differences according to gender and previous experience in robotics programming, and (3) identify profiles that would allow us to analyse the differences between them and the dimensions of computational thinking. For this purpose, the Computational Thinking Test (CTT) was used. The results of the t-tests revealed that men obtained better results than women and that previous experience in robotics programming is a determining factor in the level of development of the CTT. Furthermore, by means of a two-stage cluster analysis, three profiles were identified among the prospective teachers. The statistical analysis revealed that women who had previous experience and had used programming languages at some point had the best results in the CTT. These findings underline the importance of integrating computational thinking into the training of prospective teachers and adapting teaching strategies according to the specific needs of each group of students.